Tell your truth an advocacy campaign for male Filipino victims of child sexual abuse, to empower them, inspire them to disclose their experiences, and seek recovery through professional help - Publico, Andrei Stephen H.
Child sexual abuse is a persistent social issue that affects the lives of children all over the world, and has the potential to cause irrevocable psychological damage to victims for the rest of their lives. The Philippines in particular has become infamous for being a hotspot for the production of child pornography, and recent studies conducted throughout the country have revealed that male children are being abused at rates higher than the female children.